The Reputation Economy Understanding Knowledge Work in Digital Society - Gandini, Alessandro (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
Exploring the new professional scenes in digital and freelance knowledge, this innovative book provides an account of the subjects and cultures that pertain to knowledge work in the aftermath of the creative class frenzy. Including a broad spectrum of empirical projects, The Reputation Economy documents the rise of freelancing and digital professions and argues about the central role held by reputation within this context, offering a comprehensive interpretation of the digital transformation of knowledge work. The book shows how digital technologies are not simply intermediating productive and organizational processes, allowing new ways for supply and demand to meet, but actually enable the diffusion of cultural conceptions of work and value that promise to become the new standard of the industry.